2017
DOI: 10.1002/jcb.25909
|View full text |Cite
|
Sign up to set email alerts
|

Extracellular Nucleotide Hydrolysis in Dermal and Limbal Mesenchymal Stem Cells: A Source of Adenosine Production

Abstract: Human Limbal (L-MSCs) and Dermal Mesenchymal Stem Cell (D-MSCs) possess many properties that increase their therapeutic potential in ophthalmology and dermatology. It is known that purinergic signaling plays a role in many aspects of mesenchymal stem cells physiology. They release and respond to purinergic ligands, altering proliferation, migration, differentiation, and apoptosis. Therefore, more information on these processes would be crucial for establishing future clinical applications using their different… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
21
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 23 publications
(22 citation statements)
references
References 49 publications
1
21
0
Order By: Relevance
“…The above-described sets of experiments allowed the formulation of a general conclusion that the high 5′-NT activity is characteristic of MSCs presenting a high proliferative potential and susceptibility to the positive, stimulatory effect of Ado. The ecto-NTPDases activity on the surface of these cells is negligible (Iser et al, 2014;Kerkelä et al, 2016;Naasani et al, 2017;Roszek, Bomastek et al, 2013). MSCs from different murine tissues and also showed that these discrepancies are related to differential ecto-NTPDase (CD39) and ecto-5′-NT (CD73) expression profile of these cells.…”
Section: Proliferation and Viability Of Mscsmentioning
confidence: 97%
See 2 more Smart Citations
“…The above-described sets of experiments allowed the formulation of a general conclusion that the high 5′-NT activity is characteristic of MSCs presenting a high proliferative potential and susceptibility to the positive, stimulatory effect of Ado. The ecto-NTPDases activity on the surface of these cells is negligible (Iser et al, 2014;Kerkelä et al, 2016;Naasani et al, 2017;Roszek, Bomastek et al, 2013). MSCs from different murine tissues and also showed that these discrepancies are related to differential ecto-NTPDase (CD39) and ecto-5′-NT (CD73) expression profile of these cells.…”
Section: Proliferation and Viability Of Mscsmentioning
confidence: 97%
“…It is worth pointing out that, on their surface, MSCs express different ectonucleotidases that metabolize extracellular ATP and other nucleotides, hence modulating the purinergic signaling dynamics (Naasani et al, ; Noronha‐Matos & Correia‐de‐Sá, ; Roszek, Błaszczak et al, ; Roszek, Bomastek et al, ; Roszek et al, ; Scarfì, ).…”
Section: Purinergic Signaling System In Mscsmentioning
confidence: 99%
See 1 more Smart Citation
“…In contrast, MSCs had low CD39 and low A2AR expression but high CD73 expression. The observed differences between BM-MSCs, LA-MSCs and CB-MSCs may relate to differences in nucleotide hydrolysis activity [ 32 ]. In contrast to our data, other authors detected CD39 expression in MSCs.…”
Section: Discussionmentioning
confidence: 99%
“…Ectonucleotidase activity was measured in the cells as described previously [ 32 ]. Briefly, cells were seeded at 10,000 cells/cm 2 in 24-well plates and then incubated for 24 h. ATP, ADP and AMP (1 mM; Santa Cruz) were then added in phosphate-free buffer and incubated for either 1 h (ATP and ADP) or 30 min (AMP).…”
Section: Methodsmentioning
confidence: 99%